The message of Obadiah, Nahum and Zephaniah: the kindness and severity of God - Bridger, Gordon A. (The Bible speaks today, 2010)
These Old Testament books teach us some major truths: the importance of focusing on God, who is personal, sovereign, righteous and loving; of facing up to sin and judgment; of responding in repentance and faith; and of the hope of future salvation and restoration--From publisher description